Characterization of coarse aggregate morphology and its effect on rheological and mechanical properties of fresh concrete. (7th June 2021) - Zhao, Yu; Duan, Yihang; Zhu, Lingli; Wang, Youkai; Jin, Zhenghao
Highlights: Morphological characteristics of coarse aggregate were quantified. The effect of coarse aggregate morphological on rheological properties was studied. The effect of coarse aggregate morphological on mechanical properties was studied. The influence weight of coarse aggregate quantization parameters was characterized. The model with coarse aggregate morphological parameters as variables was established. Abstract: In order to clarify the influence of coarse aggregate morphology on the rheological property and mechanical property of fresh concrete, the morphological characteristics of coarse aggregate were quantitatively characterized, the core parameters of coarse aggregate morphology were screened, the standard parameters for quantitative characterization of coarse aggregate morphology were established, and the influence of coarse aggregate morphology on the rheological property and mechanical property of fresh concrete was explored. The results show that among the 8 parameters that represent the morphological characteristics of coarse aggregate, the flatness, angularity and roughness of aggregate have the greatest influence on the rheological properties and mechanical properties of fresh concrete. The weight of flatness on plastic viscosity is 50.54%, the weight of angularity on 28 days compressive strength is 48.95%, the weight of roughness on yield stress and flexural strength is 52.69% and 64.12%. When only the morphological composition of coarse aggregate is changed, the yield stress and plastic viscosity show the opposite variation law, the greater the yield stress, the smaller the plastic viscosity, and vice versa. When coarse aggregate with flatness less than 0.2 and roughness more than 0.4 are excluded, the yield stress is reduced by 28.58%, the plastic viscosity is increased by 23.15%, and the compressive strength is still over 60 MPa. The quantitative characterization of the coarse aggregate based on the characteristic parameters can provide a more effective method for researchers to predict the influence of coarse aggregate on the rheological properties and mechanical properties of concrete.